Bio-augmentation to improve lactic acid production from source-sorted organic household waste. (10th January 2021) - Zhang, Zengshuai; Tsapekos, Panagiotis; Alvarado-Morales, Merlin; Angelidaki, Irini
Abstract: The high and easy degradable sugar content of source-sorted organic household (SSOHW) suggests it as a promising candidate for fermentative lactic acid production. The present study aimed to apply bio-augmentation strategy with different lactic acid bacteria ( Lactobacillus delbrueckii or Pediococcus acidilactici ) to improve lactic acid production from non-sterile SSOHW. The optimum operational temperature, initial pH and total solid loading during fermentation were essential for lactic acid production. Lactic acid concentration of 20.7 ± 0.3 and 16.8 ± 0.4 g/L were obtained by bio-augmenting Pediococcus acidilactici and Lactobacillus delbrueckii, respectively, achieving an increment of 36.2% and 10.5% compared to abiotic augmentation. A lactic acid yield of 0.73 g/g-sugar was achieved with addition of Pediococcus acidilactici, while the optical purity of LA was also improved by the bio-augmentation. Furthermore, response surface methodology along with the Box-Behnken model was applied to determine the optimal operational conditions (i.e. temperature, initial pH and total solid loading). Based on the outcome, the highest concentration and yield were 31.2 g/L and 0.735 g/g-sugar at temperature of 32.4 °C, initial pH of 8.0 and total solid loading of 105.0 g/L. Finally, the predicted value was validated by scale-up experiment, and the LA titer and yield of scale-up fermenter were well corresponding to predicted value. The bio-augmentation strategy and process optimization provided a simple and energy saving method for industrial LA production from SSHOW. With respect to environmental sustainability and cleaner production, the conversion of bio-waste to lactic acid is an advantageous waste management approach that will contribute to the transition from a petro-based economy towards the production and use of bio-based derived products thereby creating innovative value chains with lower carbon footprint and social responsibility. Graphical abstract: Image 1 Highlights: Household waste is a promising candidate for fermentative lactic acid production. Bio-augmentation strategy improved the lactic acid production. Lactic acid yield of 0.73 g/g-sugar was obtained with non-sterile household waste. The optical purity of lactic acid was improved by bio-augmentation strategy.